Enhancing the Performance of a Telemedicine Node Using Intelligent-Based Adaptive Mechanism - Okafor Chika Paulinus; Muoghalu Chidiebere N.; Iloh Johnpaul I.; Achebe Patience N. (Darul Yasin Al Sys, 2026)
Reliable dish-antenna positioning is essential for satellite communication between healthcare personnel and patients through distributed mobile telemedicine nodes. However, the conventional Proportional–Integral–Derivative (PID)-based positioning system used on mobile telemedicine vehicles communicating via NigComSat-1R in Nigeria experiences performance degradation as communication delays increase and cannot adapt effectively to parameter variations, changing operating conditions, and nonlinear uncertainties. This study aims to enhance the performance of satellite dish-antenna positioning for distributed mobile telemedicine nodes using an intelligent adaptive control mechanism. A dynamic model of the antenna positioning system was developed, followed by the design of a Model Reference Adaptive Control (MRAC) method augmented with a Fuzzy Logic Control (FLC) algorithm, hereafter termed MRAC–FLC. The proposed controller was integrated into the positioning system and evaluated in a MATLAB/Simulink simulation environment. The conventional PID-controlled system exhibited a rise time of 85.9896 s and a settling time of 153.6396 s under communication delay. By comparison, the MRAC–FLC system achieved a rise time of 8.2215 s and a settling time of 16.1065 s. The proposed system also provided a smoother control response and improved overshoot performance compared with the conventional PID controller. These findings demonstrate that integrating MRAC with FLC substantially improves the transient response of the antenna positioning system. The enhanced response can facilitate faster antenna tracking and stabilization during satellite communication, thereby supporting more efficient information exchange in distributed mobile telemedicine services.